PERFORMED FACTORS IN THE REHABILITATION OF CARDIAC PATIENTS ON AN OUTPATIENT BASIS - О.I. Tokarenko; O.V. Kovaleva; A.A. Kovaleva; O.O. Tokarenko (Сучасні медичні технології)
In older people, adequate pharmacological tactics when using modern antihypertensive drugs and their combinations, which provide maximum cardiovascular protection, can increase the duration and improve the quality of life, significantly reduce the likelihood of complications. An increase in the tone of the sympathetic nervous system leads to biliary dyskinesia by hypokinetic type, an increase in blood pressure.